Effects of Macro- and Microelements in Soil of Rose Farms in Taif on Essential Oil Production by Rosa damascena Mill. - Mohamed Shohayeb; Hassan Arida; El-Sayed S. Abdel-Hameed; Saleh Bazaid (Journal of Chemistry)
Rose is one of the most economically important ornamental crops in the world. In this study, we analyzed nine macro- and microelements in soils and petals of R. damascena Mill. cultivated in Shafa and Hada mountains. The amounts of the investigated macro- and microelements varied from one soil or petal sample to another and they were generally higher in most soil and petal samples of Shafa compared to Hada. On the other hand, the levels of the investigated elements in petal samples were not dependent on their levels in soil samples. While water extracts of the soil of farms of Shafa were slightly alkaline (pH 7.69), they were moderately alkaline (pH 8.04) in Hada farms. The amounts of oil produced by rose petals of Hada were relatively larger than those of Shafa. Amongst the five investigated constituents of the volatile oil of roses, the amounts of citronellol, geraniol, and eugenol were significantly larger in the volatile oil of rose petals of Hada compared to Shafa. This study suggests that the ecology of roses of both Hada and Shafa mountains is different and this is most likely reflected on the amount of volatile oil and its constituents. Therefore, further integrated multidisciplinary research correlating rose ecology, agronomy, and essential oil yield is highly recommended.